The Relationship Between Emotional Intelligence and Learning Achievement Of Grade VIII Students - Manullang, Ruth S P; Aritonang, Nancy Naomi (CV Putra Publisher, 2026)
This study aims to find out The Relationship Between Emotional Intelligence and Learning Achievement of Class VIII Students of SMP Negeri 4 Muara, North Tapanuli Regency, Academic Year 2024/2025. Based on the results of research and discussion that have been described regarding the relationship between emotional intelligence and learning achievement in students of SMP Negeri 4 Muara, several conclusions can be drawn as follows: The emotional intelligence of students of SMP Negeri 4 Muara is in the medium to high category. This shows that most students have basic abilities in recognizing their own emotions, managing emotions, being optimistic, empathetic, and building social relationships with others. However, there are still a small number of students who are in the low category, especially in the aspect of emotional management. The learning achievement of students of SMP Negeri 4 Muara is in the high category. These results indicate that academically students have been able to achieve good learning outcomes in accordance with the standards set by the school. There is no significant relationship between emotional intelligence and learning achievement. The results of the Pearson Product Moment correlation test show a significance value greater than 0.05, so the hypothesis stating that there is a relationship between emotional intelligence and learning achievement is rejected. Thus, the high or low level of emotional intelligence of students does not directly influence the learning achievements they achieve.